The Triple Jags of Dietary Fibers in Cereals: How Biotechnology Is Longing for High FiberGrains - Botticella, Ermelinda; Savatin, Daniel Valentin; Sestili, Francesco (Frontiers in Plant Science, 2021)
Cereals represent an important source of beneficial compounds for human health, such as macro- and micronutrients, vitamins, and bioactive molecules. Generally, the consumption of whole-grain products is associated with significant health benefits, due to the elevated amount of dietary fibre (DF). However, the consumption of whole-grain foods is still modest compared to more refined products. In this sense, it is worth focusing on the increase of DF fractions inside the inner compartment of the seed, the endosperm, that represents the main part of the derived flour. The main components of the grain fibre are arabinoxylan (AX), -glucan (G), and resistant starch (RS). These three components are differently distributed in grains, however, all of them are represented in the endosperm. AX and G, classified as non-starch polysaccharides (NSP), are in cell walls, whereas, RS is in the endosperm, being a starch fraction. As the chemical structure of DFs influences their digestibility, the identification of key actors involved in their metabolism can pave the way to improve their function in human health. Here, we reviewed the main achievements of plant biotechnologies in DFs manipulation in cereals, highlighting new genetic targets to be exploited, and main issues to face to increase the potential of cereals in fighting malnutrition.